2018
DOI: 10.18060/21635
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Refugee Poverty Using Capabilities Versus Commodities: The Case of Afghans in Iran

Abstract: This study is among the first to calculate poverty among one of the world’s largest refugee populations, Afghans in Iran. More importantly, it is one of the first to use capability and monetary approaches to provide a comprehensive perspective on Afghan refugees’ poverty. We estimated poverty using data collected from a sample of 2,034 refugee households in 2011 in Iran. We utilized basic needs poverty lines and the World Bank’s absolute international poverty line for our monetary poverty analyses and the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Reports suggest that over 80% of Afghans in Iran have access to a durable, sheltered living space with minimum standards of living [ 42 ]. Where a study of livelihood of Afghan refugees in Iran had found half of the households to have only poor income; of those, only 60% were not deprived from minimal education, health, and standards of living, based on the multidimensional poverty index (MPI) that is used for capability analyses of poverty criteria [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that over 80% of Afghans in Iran have access to a durable, sheltered living space with minimum standards of living [ 42 ]. Where a study of livelihood of Afghan refugees in Iran had found half of the households to have only poor income; of those, only 60% were not deprived from minimal education, health, and standards of living, based on the multidimensional poverty index (MPI) that is used for capability analyses of poverty criteria [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent improvements, the added tuition fees as part of the code of conduct for the education of Afghans continue to limit access for many Afghan children to Iranian schools. A significant number of Afghan households in Iran live in poverty (Naseh, Potocky, Burke, & Stuart, 2018). The decline in Iran's economy and the COVID-19 pandemic has further limited the financial ability of Afghan households and consequently the access of Afghan children to education in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…National context in place to encourage and occasionally force repatriation of Afghans (Naseh, Potocky, Burke, & Stuart, 2018). During these years almost all self-governed Afghan schools were closed down by the government with the justification that these schools are providing low-quality education in unsafe settings (Herve, 2018).…”
Section: Name Of the Policy (Date) Policy Change (Decision Maker) Con...mentioning
confidence: 99%
See 2 more Smart Citations